2004
DOI: 10.1089/1044549041562267
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids Are FXR Ligands and Differentially Regulate Expression of FXR Targets

Abstract: Polyunsaturated fatty acids (PUFAs) have been previously reported as agonists of peroxisome proliferatoractivated receptor and antagonists of the liver X receptor. The activities on these two nuclear receptors have been attributed to their beneficial effects such as improvement of dyslipidemia and insulin sensitivity and decrease of hepatic lipogenesis. Here we report that PUFAs are ligands of farnesoid X receptor (FXR), a nuclear receptor for bile acids. In a conventional FXR binding assay, arachidonic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 46 publications
5
58
1
1
Order By: Relevance
“…Thus, distinct from rosiglitazone and pioglitazone, troglitazone acted as a dual ligand for both PPAR␥ and FXR. Similar overlapping ligand specificity phenomenon has also been reported for a class of polyunsaturated fatty acids, including arachidonic acid, docosahexaenoic acid, and linolenic acid (Zhao et al, 2004). Those polyunsaturated fatty acids are endogenous agonists of PPAR, antagonists of nuclear receptor liver X receptor, and ligands of FXR differentially modulating FXR target gene expression.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, distinct from rosiglitazone and pioglitazone, troglitazone acted as a dual ligand for both PPAR␥ and FXR. Similar overlapping ligand specificity phenomenon has also been reported for a class of polyunsaturated fatty acids, including arachidonic acid, docosahexaenoic acid, and linolenic acid (Zhao et al, 2004). Those polyunsaturated fatty acids are endogenous agonists of PPAR, antagonists of nuclear receptor liver X receptor, and ligands of FXR differentially modulating FXR target gene expression.…”
Section: Discussionsupporting
confidence: 71%
“…Studies have demonstrated that the FXR can also be activated via triterpenoids (e.g. forskolin) (Zhao et al, 2004) and polyunsaturated fatty acids (e.g. arachidonic acid) (Iser et al, 1975).…”
Section: Farnesoid X Receptor (Fxr)mentioning
confidence: 99%
“…It has been previously reported that polyunsaturated fatty acids, specifically arachidonic acid and docosahexaenoic acid (DHA) are ligands for hFXR␣, and modulate BSEP expression (33). Because skate hepatocytes contain a high content of lipids, including DHA (24), we tested whether polyunsaturated fatty acids could activate sFxr.…”
Section: Skate Fxr Identification and Tissue Distributionmentioning
confidence: 99%